Why do Taiwanese young adults not jump on the bandwagon of Pokémon Go? Exploring barriers of innovation resistance - Jeffry Oktavianus; Helena Oviedo; Winiber Gonzalez; Andriani Pratama Putri; Trisha T. C. Lin (International Telecommunications Society (ITS), 2017)
Despite the unprecedented global diffusion of Pokémon Go, some refuse to jump on the bandwagon of this augmented reality (AR) mobile gaming. This exploratory study conducts in-depth interviews with 30 non-adopters (discontinuers and resistors), after the gaming experienced setbacks, in order to identify the factors affecting young Taiwanese smartphone users and gamers' innovation resistance. The results show physical and time risk concerned both groups of non-adopters when they got addicted to Pokémon Go, pinpointing the significance of physical danger and temporal issues in relation to innovation resistance. Discontinuers and resistors had further distinct reasons for resisting the game. Usage barrier had a strong impact on discontinuers. Playing the game is not compatible with their schedule, leading them to stop playing Pokémon Go. While image barrier was the prominent factor for resistors. Even without playing the game, they perceived the game negatively leading them to refuse to play the game.
Keywords: 330; Pokémon Go; innovation resistance; usage barrier; value barrier; risk barrier; tradition barrier; image barrier; social barrier; resistor; discontinuer